Microbial Degradation of Lignocellulose in Empty Fruit Bunch at Various Incubation Time - Noverando Rafiel Angelo; Rudiyansyah Rudiyansyah; Gusrizal Gusrizal (Journal of Tropical Biodiversity and Biotechnology, 2022)
Isolation of cellulose in empty fruit bunch (EFB) is hindered by lignin content. EFB was pretreated with Pleurotus ostreatus which has the ability to degrade lignin, in various incubation times (0th, 15th,30th, 45th, and 60th). The result showed lignin and cellulose decreased from 29.3% to 20.3% and from 40.2% to 26.2%, respectively. The optimum degradation time was on 30th day in which lignin and cellulose contents decreased from 29.3% to 20.3% and from 41% to 39.7% respectively. The cellulose to lignin (C/L) ratio increased from 1.40 to 1.99. These data revealed that P. ostreatus have a high potential for EFB delignification.